The current status of various preclinical therapeutic approaches for tendon repair - Wenqing Liang; Chao Zhou; Yongjun Deng; Lifeng Fu; Jiayi Zhao; Hengguo Long; Wenyi Ming; Jinxiang Shang; Bin Zeng (Annals of Medicine, 2024)
AbstractTendons are fibroblastic structures that link muscle and bone. There are two kinds of tendon injuries, including acute and chronic. Each form of injury or deterioration can result in significant pain and loss of tendon function. The recovery of tendon damage is a complex and time-consuming recovery process. Depending on the anatomical location of the tendon tissue, the clinical outcomes are not the same. The healing of the wound process is divided into three stages that overlap: inflammation, proliferation, and tissue remodeling. Furthermore, the curing tendon has a high re-tear rate. Faced with the challenges, tendon injury management is still a clinical issue that must be resolved as soon as possible. Several newer directions and breakthroughs in tendon recovery have emerged in recent years. This article describes tendon injury and summarizes recent advances in tendon recovery, along with stem cell therapy, gene therapy, Platelet-rich plasma remedy, growth factors, drug treatment, and tissue engineering. Despite the recent fast-growing research in tendon recovery treatment, still, none of them translated to the clinical setting. This review provides a detailed overview of tendon injuries and potential preclinical approaches for treating tendon injuries.